PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 168 PEKANBARU - Siti Nurasiah; Erlisnawati '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: This research is a class Action Research that aims to increase the social studies IV SDN 168 Pekanbaru through Application of Cooperative Learning Model Type Think Pair Share (TPS). Based on the observations made in the classroom Build IV SDN 168 Pekanbaru is known that student learning outcomes is low which of 39 students, only 15 students (38.46%), which reached a minimum value of mastery criteria (KKM) is 70, while 24 students (61.54%) who did not achieve a minimum completeness criteria. Based on the analysis and test study showed that the application of Model Cooperative Learning Type Think Pair Share (TPS) can improve learning outcomes studies fourth graderes SDN 168 Pekanbaru. Technical analysis of the data used by researchers to measure learning outcomes is through the first daily test on the first cycle, the second daily test on the second cycle and the third daily test on the third cycle. The average score was 60.41 basis of social studies, the increase in the first cycle with an average of 68,20, the second cycle with an average of 74.35. hus the increase of the base score to the first cycle is 6%, from the second cycle to the base score is 12,15%. researchers also provide observation sheet to observe the activities of teachers and students during the learning takes place. The results of observations of teacher activity in the first cycle 1 meeting received an average score of 67%, meeting 2 received an average score of 71%, in the second cycle 1 meeting received an average score of 88%, meeting 2 average score of 92%. percentage of student learning activities in the first cycle was 58.3% 1 meeting, meeting 2 was 66%, in the second cycle 1 meeting a percentage of 83%, meeting 2 is 88%. From these results it can be concluded that the application of Model Cooperative Learning Type Think Pair Share (TPS) can improved Student Achievement Social Studies Fourth graderes SDN 168 Pekanbaru.Keywords : Cooperative Learning Model Type TPS , Learning Outcomes IPS